Social Phobia Is Associated with Delayed Onset of Chickenpox, Measles, and Mumps Infections - Ajdacic-Gross, Vladeta; Aleksandrowicz, Aleksandra; Rodgers, Stephanie; Müller, Mario; Kawohl, Wolfram; Rössler, Wulf; Castelao, Enrique; Vandeleur, Caroline; von Känel, Roland; Mutsch, Margot; Lieb, Roselind; Preisig, Martin (Frontiers in Psychiatry, 2016)
Objective: Evidence showing that infectious diseases in childhood play an important role in the etiopathogenesis of neurodevelopmental and other mental disorders is growing. The aim of this study was to explore the timing of common childhood diseases in early-onset anxiety disorders. Materials and Methods: We analyzed data from PsyCoLaus, a large Swiss Population Cohort Study (N=3720). In this study, we regressed overanxious disorder, separation anxiety disorder, social phobia and specific phobias on the age of onset of several childhood diseases, always adjusting for the other anxiety disorders listed above and for sex. Results: The timing of viral childhood diseases (chickenpox, measles and mumps) was consistently delayed in social phobia, notably both in men and women. We found no evidence for a reversed sequence of onset of phobia symptoms before that of the infections included. Conclusions: Social phobia was the only early anxiety disorder to show an association with a delayed onset of common viral childhood diseases.